Implications of diet-induced obesity on metabolic and immune homeostasis: the role of the mesenteric lymph nodes - Hill, Jessica Lynn, author; Foster, Michelle T., advisor; Weir, Tiffany L., committee member; Gentile, Christopher L., committee member; Schenkel, Alan, committee member (Colorado State University. Libraries, 2020)
Obesity is a major public health crisis among adolescents and adults. The development of obesity is associated with several comorbidities as a result of underlying systemic chronic inflammation, the culmination of which increases one’s risk for chronic and infectious disease. Excessive accumulation of visceral adipose tissue is shown to confer the greatest disease risk. This is primarily due to inherent depot differences, namely proximity to and a shared blood supply with the liver and gastrointestinal (GI) tract. Recent work demonstrates the considerable influence gut physiology has over both local and systemic homeostasis, as GI diseases such as inflammatory bowel disease are associated with metabolic derangements characteristic of obesity. While the mechanisms that mediate this inter-organ crosstalk continue to be elucidated, several studies suggest that inflammation originating from the gut triggers these broad metabolic and immunologic changes found in obesity. Previous work from our lab has demonstrated that high-fat diet (HFD) induced obesity results in mesenteric lymph node (MLN) fibrosis, which was associated with a localized impairment in immune function. MLNs, located within mesenteric adipose tissue (MAT) surrounding the GI tract, constitutively monitor the mesenteric adipose depot and draining sections of the small and large intestines, serving as critical inductive sites for adaptive immune responses. Subsequently, they are essential for overall tissue maintenance and protection. Hence, further study into the role of the MLNs in obesity-associated pathology is an important area of research. The goals of this dissertation research were to 1) examine the relationship between MLNs and GI inflammation on metabolic outcomes, and 2) characterize immunologic changes associated with models of chronic inflammation. To investigate the above-mentioned, we conducted four separate preclinical studies utilizing mouse models of diet-induced obesity, MLN cauterization, and dextran sulfate sodium (DSS) induced GI inflammation. In the first study (Chapter 2), we examined the contribution of the MLNs on disease pathology associated with HFD-induced obesity. We found that MLN dysfunction, either as a result of surgical manipulation or obesity-induced fibrosis, led to metabolic dysfunction. Furthermore, that functional MLNs are needed for the full restorative effects of Pirfenidone treatment. In the second study (Chapter 3), we examined the effect of chronic low-dose DSS induced GI inflammation, independent of diet and obesity, on metabolic and immune function. We found that non-obese mice treated with DSS had a modest reduction in total body weight and MAT mass yet showed substantial alterations in tissue immune cell populations and frequencies. These adaptations occurred without a concurrent change in glucose homeostasis. Finally, in the third study (Chapter 4) we characterized immunologic parameters within a normal weight and obese human population, free of disease, through the ex vivo challenge of peripheral blood mononuclear cells (PBMCs) with the T lymphocyte mitogen Concanavalin A (ConA). We found that PBMCs isolated from obese adults had a modest increase in cell proliferation and IFNγ secretion upon stimulation within ConA relative to their normal weight controls. Additionally, we found a distinct expansion of CD4+CD8+ T cells, CD16+ monocytes, and NK cells within ConA stimulated PBMCs from obese donors. Collectively, these studies provide evidence that 1) the MLNs are critical for metabolic homeostasis as their dysfunction exacerbates features of HFD-induced obesity; 2) chronic GI iv inflammation, independent of diet and obesity, can reshape the immune milieu without altering glucose homeostasis; and 3) obesity distinctly alters the PBMC response to acute ex vivo challenge as compared to that of normal weight individuals. Future studies should further elucidate mechanisms of crosstalk between the immune system, MLNs, and GI tract on metabolic homeostasis in models of obesity.